Konsep Kurikulum Merdeka Dalam Pendidikan - Atin Srihandayani; Meylina Astuti; Ratna Sari; Mustafiyanti Mustafiyanti (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
At the National Teacher's Day commemoration event in 2019 the Minister of Education and Culture or the Ministry of Education and Culture initiated the concept of